Continuous-variable QKD over 50 km commercial fiber. (29th May 2019) - Zhang, Yichen; Li, Zhengyu; Chen, Ziyang; Weedbrook, Christian; Zhao, Yijia; Wang, Xiangyu; Huang, Yundi; Xu, Chunchao; Zhang, Xiaoxiong; Wang, Zhenya; Li, Mei; Zhang, Xueying; et al.
Abstract: The continuous-variable version of quantum key distribution (QKD) offers the advantages (over discrete-variable systems) of higher secret key rates in metropolitan areas, as well as the use of standard telecom components that can operate at room temperature. An important step in the real-world adoption of continuous-variable QKD is the deployment of field tests over commercial fibers. Here we report two different field tests of a continuous-variable QKD system through commercial fiber networks in Xi'an and Guangzhou over distances of 30.02 km (12.48 dB) and 49.85 km (11.62 dB), respectively. We achieve secure key rates two orders-of-magnitude higher than previous field test demonstrations by employing an efficient calibration model with one-time evaluation. This accomplishment is also realized by developing a fully automatic control system which stabilizes system noise, and by applying a rate-adaptive reconciliation method which maintains high reconciliation efficiency with high success probability in fluctuated environments. Our results pave the way for the deployment of continuous-variable QKD in metropolitan settings.